Pengaruh Panjang Serat Pelepah Kelapa Sawit dan Persentase Serbuk Cangkang Telur terhadap Kekuatan Impak Komposit Bermatriks Polyester - Aidil Pratama; Juanda Juanda; Ilham Ary Wahyudie; Sukanto Sukanto; Amril Reza (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Utilising oil palm frond fibre and eggshell powder provides an opportunity to convert plantation and food waste into functional composite constituents. This study examined the effects of fibre length and eggshell-powder content on the Charpy impact strength of a polyester-matrix composite. A 3 × 3 full-factorial design was applied using fibre lengths of 60, 70, and 80 mm and eggshell-powder contents of 3, 6, and 9 wt.%. Three specimens were prepared for each combination by hand lay-up, giving 27 specimens, and were tested with reference to ISO 179-1. The highest mean impact strength was 50.72 kJ/m² for the 80 mm–9% combination, whereas the lowest was 15.52 kJ/m² for the 80 mm–6% combination. Two-way ANOVA indicated significant effects of fibre length, eggshell-powder content, and their interaction (p < 0.001). The interaction confirms that a longer fibre does not automatically improve impact strength unless it is accompanied by an appropriate filler content. The investigated composite is therefore positioned as an initial candidate for car bumper components.